Concurrent Resolution of Chronic Diarrhea Likely Due to Crohn’s Disease and Infection with Mycobacterium avium paratuberculosis - Singh, Shoor V.; Kuenstner, J. Todd; Davis, William C.; Agarwal, Prabhat; Kumar, Naveen; Singh, Devendra; Gupta, Saurabh; Chaubey, Kundan K.; Kumar, Ashok; Misri, Jyoti; Jayaraman, Sujatha; Sohal, Jagdip S.; et al. (Frontiers in Medicine, 2016)
Examination of samples of stool from a 61 year old male patient, presenting with the clinical symptoms of Crohn’s disease (CD), revealed massive shedding of acid fast bacilli with the morphology of Mycobacterium avium paratuberculosis (MAP), the causative agent of Johne’s disease in cattle. MAP was cultured from the stool. Biotyping of the bacterium isolated from cultures of stool demonstrated it was the Indian Bison biotype of MAP, the dominant biotype infecting livestock and humans in India. Based on this finding and because the patient was unresponsive to standard therapy used in India to treat patients with gastrointestinal inflammatory disorders, the patient was placed on a regimen of multi-antibiotic therapy, currently used to treat tuberculosis and CD. After one year of treatment, the patient’s health was restored, concurrent with cessation of shedding of MAP in his stool. This patient is the first case shown to shed MAP from the stool who was cured of infection with antibiotics and who was concurrently cured of clinical signs of CD.